2020
DOI: 10.2144/fsoa-2020-0034
|View full text |Cite
|
Sign up to set email alerts
|

ITGA4 Gene Methylation Status in Chronic Lymphocytic Leukemia

Abstract: Background: We aimed to investigate ITGA4 gene expression pattern and to explore its methylation heterogeneity in chronic lymphocytic leukemia (CLL). Patients & methods: Eighty one CLL patients and 75 healthy subjects were enrolled and prognostic evaluation of patients was assessed. ITGA4 q-realtime PCR was performed using Applied Biosystems, TaqMan gene expression assay. ITGA4 gene-specific CpG methylation was investigated in real time using pyrosequencing technology. Results: ITGA4 was differentially exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…However, few reports have shown the roles of ITGA4 , BAD , PPP2R3A , CPT1B , ACACB , CACNA1S , CACNG1 , and MAPK12 in cartilage injury repair. ITGA4 encodes a member of the integrin α chain family, and its high level is associated with many diseases, such as chronic lymphocytic leukemia [ 55 ], gastrointestinal stromal tumors [ 56 ] and colorectal cancer [ 57 ]. BAD plays a key role in mitochondria-dependent apoptosis, and its inactivation contributes to the development of rheumatoid arthritis by conferring apoptosis resistance in synovial sub lining macrophages [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, few reports have shown the roles of ITGA4 , BAD , PPP2R3A , CPT1B , ACACB , CACNA1S , CACNG1 , and MAPK12 in cartilage injury repair. ITGA4 encodes a member of the integrin α chain family, and its high level is associated with many diseases, such as chronic lymphocytic leukemia [ 55 ], gastrointestinal stromal tumors [ 56 ] and colorectal cancer [ 57 ]. BAD plays a key role in mitochondria-dependent apoptosis, and its inactivation contributes to the development of rheumatoid arthritis by conferring apoptosis resistance in synovial sub lining macrophages [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the ECM-receptor interaction was substantially enriched in 3 DEMs, including ITGA3, ITGA4 , and COL4A5 . These three genes were more closely related to diseases ( 64 66 ), but studies have found that ITGA3, ITGA4 , and COL4A1 may be involved in the composition of adipocyte extracellular matrix and the differentiation of adipocytes ( 67 ).…”
Section: Discussionmentioning
confidence: 99%
“…Opposingly, methylation of the ITGA4 gene that encodes another integrin alpha subunit (α4) is already described as a biomarker for different cancers [ 77 , 78 , 79 , 80 ], but not in PCA. Interestingly, we found that higher methylation levels of CpGs present in the first exon of ITGA4 were associated with lower gene expression and worse outcome.…”
Section: Discussionmentioning
confidence: 99%